Assistance in the Use of YouTube Kids as a Creative Learning Resource for Educators and Education Staff - Hefniy Hefniy; Nur Azizah; Fatimatus Zahro; Hasan Baharun; Moch Tohet; Faizatul Widat; Ahmad Fauzi (Al-Qalam Institute, 2025)
Children's education faces challenges in providing innovative and engaging learning methods in the digital era. The biggest challenge is the limited use of technology as a learning medium because educators are less skilled in utilizing it. In an effort to overcome this, YouTube Kids, an application specifically designed for children with educational video content, can be an effective solution. This application provides a variety of safe and age-appropriate educational videos, as well as parental control features to ensure content security. The use of YouTube Kids as a learning medium can increase student engagement, information retention, and understanding of material through interactive concept visualization. Therefore, training for educators at Darul Mubtadi'in 02 Kindergarten in utilizing YouTube Kids is very important to create a more innovative, engaging, and effective learning environment. This training aims to improve teachers' skills in using technology and digital media, as well as integrating YouTube Kids content into the curriculum, so as to provide an active, creative, and enjoyable learning atmosphere for students.